Dopuszczalność udzielania ulg w zapłacie kar pieniężnych nakładanych na podstawie ustawy o międzynarodowym przemieszczaniu odpadów - Stawiński, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article deals with the issue of administrative fines payment reliefs applicable for infringement of the provisions of legislation relating to shipments of wastes. The author analyses whether there is any legal basis for granting such reliefs. The article presents and comments on the judicial decisions made by domestic administrative courts regarding this issue. Finally, the author proposes some changes in regulations of shipment of waste.
Keywords: kara administracyjna; przemieszczanie odpadów; odpowiedzialność administracyjna; odroczenie terminu zapłaty kary administracyjnej; umorzenie kary administracyjnej; rozłożenie kary administracyjnej na raty